Is it possible to assess the "ethics" of medical school applicants?. Issue 6 (1st December 2001) - Lowe, Michael; Kerridge, Ian; Bore, Miles; Munro, Don; Powis, David
Abstract : Questions surrounding the assessment of medical school applicants' morality are difficult but they are nevertheless important for medical schools to consider. It is probably inappropriate to attempt to assess medical school applicants' ethical knowledge, moral reasoning, or beliefs about ethical issues as these all may be developed during the process of education. Attitudes towards ethical issues and ethical sensitivity, however, might be tested in the context of testing for personality attributes. Before any "ethics" testing is introduced as part of screening for admission to medical school it would require validation. We suggest a number of ways in which this might be achieved.